The Influence of Product Variation, Taste Variation, and Hygiene on Purchasing Decisions at Simple Restaurants in Bengkulu - Muhammad Maisal Lailamsyah (Yayasan Darussalam Bengkulu, 2024)
To find out how much influence product variations have on purchasing decisions at the Bengkulu Simple Restaurant, To find out how much influence the taste variations have on purchasing decisions at the Bengkulu Simple Restaurant, To find out how much hygiene influences purchasing decisions at the Bengkulu Simple Restaurant, To find out how much There is a big influence of product variations, taste variations, and hygiene on purchasing decisions at the Bengkulu Simple Restaurant. This research method is exploratory. Exploratory research, or also called exploratory research, is a research approach that aims to find information about a topic/problem that is not yet fully understood by a researcher. Exploratory research does not require a specific hypothesis or theory. The researcher only prepared several questions as a guide to obtain primary data in the form of information, information, as initial data needed. Based on the results, there is an influence of product variations (X1) on consumer purchasing decisions (Y) for Rumah Makan Simplified Bengkulu with a tsig value of 0.000 < 0, 05 and the value of tcount > ttable is 5.764 > 1.65765, thus Ho is rejected and Ha is accepted. From the significance value obtained, variable X influences consumer purchasing decisions (Y). There is an influence of taste variation (X2) on consumer purchasing decisions (Y) at the Bengkulu Simple Restaurant with a tsig value of 0.001 < 0.05 and a tcount > ttable value of 2.240 > 1.65765, thus Ho is rejected and Ha is accepted. From the significance value obtained, the variable X2 influences consumer purchasing decisions (Y). There is a hygienic influence (X3) on consumer purchasing decisions (Y) at the Bengkulu Simple Restaurant with a tsig value of 0.000 and a tcount > ttable value of 5.734 > 1.65765, thus Ho is rejected and Ha is accepted. From the significance value obtained, variable X3 influences consumer purchasing decisions (Y). Product variations, taste variations and hygiene together show an influence on purchasing decisions. The test results show a significance value <0.05.